Factores de riesgo psicosocial intralaboral presentes en los funcionarios de facilísimo Red de Servicios del Qundío S.A. (2020)
Work influences employee health, so it is important to assess the factors psychosocial risk. The objective of this research was to describe the risk factors borr labor social psychosocial present in the officials of Easy Service Network S. A. It was developed from a quantitative-descriptive methodology, with a sample of 30 workers. The Battery was used for the assessment of psychosocial risk factors (intra-labor and extra-labor), and only the general data sheet (socio-demographic information and occupational information of the workers) and the questionnaire of intra-labor psychosocial risk factors (form A) were applied for that battery. Sociodemographic and occupational information showed characteristics typical of each worker, allowing to evaluate the effects of the psychosocial risks identified, and in the level of intra-labor psychosocial risk medium and high; so it is necessary to focalize plans and actions aimed at the prevention and control of them.